The 1993 Constitutional Amendment: a procedural ultra vires? / Muhammad Amir Sharipuddin … [et al.] - Sharipuddin, Muhammad Amir; Abd Rahman, Mohamad Lokman Hakim; Mostafa, Mohd Farouq; Takayudin, Mohammad Mohsen (2009)
This paper studies the legality of the 1993 Constitutional Amendment which effectively ended the Malay Rulers immunity from any legal proceedings and the corresponding questions regarding the proper procedures for amending a constitutional provision that needed the consent of the Conference of Rulers. Based from our interview and reading materials we have formed our own understanding of the subject and answered the underlying questions that the amendments brought in picture; that the proper amending procedures has not been followed and that the 1993 Constitutional Amendments is strictly speaking a procedural ultra vires.